SECOND LANGUAGE ACQUISITION CLASSROOM INTERACTION IN SL GRAMMAR AND TRANSLATION DIFFICULTIES PROBLEMATIC AREAS ENCOUNTERED BY STUDENTS ELEVENTH GRADE IN IPS CLASS OF SENIOR HIGH SCHOOL - Wirawan, Fajar; Novita, Loly; Masran, Silviana (Ensiklopedia of Journal, 2025)
Grammar is the study of all the contrasts of meaning that it is possible to make within sentences. In teaching and learning process grammar can help the teacher to communication, translation and easily interaction. Communicating point in the easiest to understand and most persuasive way possible trumps correct grammar every time. aims to find out the main factors that contribute to the existence of these difficulties.The results of this study can help the Ministry of Education, the EFL teachers, the curriculum designers, and the designers of assessment tools to understand the reasons why students in eleventh grade find difficult in grammar and translation. Two instruments were used in the present study, and they are lesson observations, and interviews. Data collected on this issue revealed that there are some major grammar and translation difficulties encountered by the students at this level. These are about grammar and translation the difficult the factors.